Paleoenvironmental context and cultural sequence for the archaeological occupation of Samaca H-8, lower valley of Ica, Peru - Santana-Quispe, Lady (2022)
The study of prehispanic ceramic of the Ica valley has allowed for the creation of a master sequence and proposal for an Andean chronology. Furthermore, it was transformed into an important tool for later studies in this area, mainly focused on the earliest periods. However, the transition between the Middle Horizon to the Late Intermediate in Andean archaeology is a process that has generated an interesting discussion. Our recent researches in the Samanca basin provide absolute and relative dates, a stratigraphic sequence, and geoarchaeological analyses that indicate the persistence of ceramic from Stage 4 of the Middle Horizon and environmental changes, that do not with any kind of archaeological gap. We conclude that Samanca H-8 was occupied continuously between c. 997-1194 AD; with the presence of Stage 4 pottery styles and Ica phase styles, that existed under environmental conditions prone to aridity.